2014
DOI: 10.1589/jpts.26.1675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Therapy on Blood Lipids of Obese Women

Abstract: [Purpose] The aim of this study was to examine the effects of exercise therapy on blood lipids of obese women. [Subjects] The subjects were 24 clinically obese women. [Methods] The subjects were divided into an exercise group (n=12), and a control group (n=12). The exercise group performed exercise for 10 weeks with diet restriction. We investigated how this type of exercise influenced blood lipids. Blood was taken before and after the intervention. The collected blood was centrifuged at 3,000 rpm for 10 minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 6 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…Maciejczyk et al 27 ) conducted an aerobics study involving male subjects, and the results were negative. Lee et al 28 ) concluded from their results that the effects of exercise therapy on blood lipids in obese women were significantly associated and shown the differences. Based on these results, it was concluded that aerobics and diet therapy can decrease BMI and body mass composition in overweight women.…”
Section: Discussionmentioning
confidence: 97%
“…Maciejczyk et al 27 ) conducted an aerobics study involving male subjects, and the results were negative. Lee et al 28 ) concluded from their results that the effects of exercise therapy on blood lipids in obese women were significantly associated and shown the differences. Based on these results, it was concluded that aerobics and diet therapy can decrease BMI and body mass composition in overweight women.…”
Section: Discussionmentioning
confidence: 97%
“…Published studies have demonstrated the positive effects of exercise training on maximal oxygen consumption (MaxVO 2 ), weight, and waist circumferences in PCOS patients 5 ) . Combined aerobic and resistance exercise is more effective than either aerobic or resistance exercise alone in improving insulin sensitivity and glycemic control and in reducing abdominal fat in obese women with PCOS 6 , 7 ) . However, the metabolic and clinical characteristics of PCOS patients who are not overweight, and thus the efficacy of the various forms of exercise, have not been evaluated 8 ) .…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely reported that an active lifestyle during childhood and adolescence optimizes growth and development 14 , 15 , 16 ) . The body mass index has also been found to be related to total percentage of body fat in both boys and girls which can be influenced by genetic predisposition and environmental factors 17 , 18 , 19 , 20 , 21 , 22 , 23 ) .…”
Section: Introductionmentioning
confidence: 99%